(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Pregnancy and childbirth is an important event in the life cycle of women and their health during this period is very much vital for the mother and children. Maternal mortality ratio (MMR) of a country is an important indicator of the overall health status of mother. Objectives: To assess the health care seeking behaviour of postnatal women in rural Bangladesh. Materials and Methods: This cross sectional study was conducted at Chaturia in Dhamrai upazilla of Dhaka district from January 2019 to March 2019 among purposively selected 196 rural women of reproductive age who had at least one living child. Data were collected by face-to-face interview using pretested questionnaire. Results: Among 196 respondents average monthly family income was 12561 Taka with SD of 10462 taka. Majority of them were housewives and about two-third (64.8%) were educated above secondary level. 70.9% respondents had their delivery of last child in a government health care center and 37.8% deliveries were conducted by nurses which was followed by government doctors (36.2%). Majority (62.2%) had their health checkup within 42 days, 59.2% of them had checkup for three or more times and the checkup were done by government doctors (60.2%). 47.1% of the respondents experienced high grade fever as postpartum complication. Statistically significant association (p<0.05) were revealed between age group of the respondents with health personnel conducted deliveries and also between educational level of the respondents with place of delivery of last child. Conclusion: Awareness, motivation and infrastructural development play a vital role in utilizing the government healthcare services by the postnatal women in rural Bangladesh. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 80-83